2005
DOI: 10.1016/j.amjhyper.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Predicts Cardiovascular Risk in Patients With Type 2 Diabetes Mellitus

Abstract: In summary, PP is a better predictor of CHD events than SBP in persons with type 2 diabetes, but the converse is true for CVD and PVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 29 publications
6
68
0
Order By: Relevance
“…Although the crosssectional design did not allow any firm conclusions regarding causality, we hypothesised that PP could be a risk factor for the progression of albuminuria in this patient group. Subsequently, several studies have associated an elevated PP with both micro- [3,5] and macrovascular [6][7][8] complications in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the crosssectional design did not allow any firm conclusions regarding causality, we hypothesised that PP could be a risk factor for the progression of albuminuria in this patient group. Subsequently, several studies have associated an elevated PP with both micro- [3,5] and macrovascular [6][7][8] complications in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated pulse pressure (PP) is strongly associated with micro- [1][2][3][4][5] as well as macrovascular [1,[6][7][8] complications in type 2 diabetic patients. In a large observational study including 954 elderly type 2 diabetic patients [9], ambulatory PP was a strong and independent predictor of progression of nephropathy during a 2 year follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…6): these increases are further amplified in the presence of micro-and macrovascular complications [61][62][63]. Importantly, the increased pulse pressure observed in type 2 diabetic patients has been found to be predictive of future cardiovascular mortality [60,64].…”
Section: Estimates Of Arterial Stiffnessmentioning
confidence: 99%
“…9 The relationship between age and PP was stronger in diabetic subjects than in non-diabetic individuals. 10 This baseline assessment of the ROADMAP study showed office PP correlations with indices of glycemic control being in a good agreement with the evidences that the metabolic alterations in type 2 diabetes are associated with increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 96%
“…8 It has also been reported that PP is independently associated with cardiovascular mortality in individuals with type 2 diabetes and PP is a better predictor of coronary heart disease (CHD) events than systolic blood pressure (SBP). [9][10][11] The results of the FinnDiane Study showed that early age-related rise in office PP was more pronounced in subjects with diabetic nephropathy, but was also evident in diabetic subjects with normal albumin excretion. 12 Recent studies indicate that ambulatory PP may provide additional information to predict progression of albuminuria in elderly diabetic subjects, above and beyond office PP.…”
Section: Introductionmentioning
confidence: 99%